DIVERSIFIKASI BAHAN HERBAL MENJADI PRODUK KECANTIKAN DI DESA NUMPUKAN, KARANGTENGAH, IMOGIRI, BANTUL - Sholihatil Hidayati; Eni Kartika Sari (LPPM IST AKPRIND Yogyakarta, 2019)
This Community Service Program aims to increase the economic value of herbal ingredients into beauty products and encourage the growth of community entrepreneurial spirit of community in Numpukan, Karangtengah, Imogiri, Bantul. In order to achieve the objectives of PKM, methods of socialization, training and assistance to the community are used. The socialization was carried out to increase the people's knowledge of the benefits of diversifying herbal ingredients into beauty products. While the training for making soap and herbal scrubs is to improve the community skills in processing herbal ingredients into beauty products. Assistance is intended to encourage the optimal use of herbal ingredients. The results of PKM activities are smooth implementation of socialization events and training for making soap and herbal scrubs. The activity was attended by 17 people. Participants directly practiced making soap and herbal scrubs. During the PKM activities there was good communication between the PKM team and the community. In addition, the assistance that has been carried out shows that some residents practice making soap and scrubs in their homes to fulfill the needs of their families even though they have not sold their products because of their daily work.